Identification of Mycobacterium bovis Isolates by a multiplex PCR - de Souza Figueiredo, Eduardo Eustáquio (Sociedade Brasileira de Microbiologia, 2009)
Isolates from suggestive bovine tuberculosis lesions were tested by a multiplex polymerase chain reaction (m-PCR) targeting for RvD1Rv2031c and IS6110 sequences, specific for M. bovis and Mycobacterium tuberculosis complex respectively. The m-PCR successfully identified as M. bovis 88.24% of the isolates.